Influence of Service Quality and Marketing Mix on Customer Satisfaction at PT BPR Pijer Podi Kekelengen Simpang Selayang - Pinem, Micael Andepa; Pujangkoro, Sugih Arto; Sembiring, Beby Karina Fawzeea Fawzeea (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Organizations must be able to predict customer needs and desires in the future accurately, so banks can develop innovative products and strategies. This research consists of Service Quality and Marketing Mix influencing Customer Satisfaction at BPR Pijer Podi Kekelengen Simpang Selayang Branch. The sample in this study was 376 savings customers of BPR Pijer Podi Kekelengen Simpang Selayang Branch Office. The analysis in this research is multiple linear regression. The partial and simultaneous research results show that the variables of Service Quality and Marketing Mix positively and significantly affect Customer Satisfaction at BPR Pijer Podi Kekelengen Simpang Selayang.